The Role of Online Learning Media in Increasing Student Achievement and Learning Motivation - R. Nurhayati; Luqman MoHa; Rizki Fiidznillah (Journal Emerging Technologies in Education, 2024)
Background. Learning media is not only in the form of books, but in this day and age, many learning media are now in online or digital form which can be used by students and teachers at school anytime and anywhere. Purpose The aim of this research is to increase student motivation and improve student achievement in online learning media. Method. This research uses quantitative methods by collecting data in the form of interviews and questionnaires distributed online. Results. The results of this research explain that online learning media has a very positive impact on the world of education. This makes teachers have to be more creativez and innovative in using online learning media to attract more students' interest in learning.   Conclusion The conclusion of this research is that the role of online learning media is very influential in increasing student motivation and student achievement. The limitation of this research is that the research only mentions suitable online learning media without looking at whether it suits the students' needs.